ChemInform Abstract: Structure Prediction of Binary Pernitride MN2 Compounds (M: Ca, Sr, Ba, La, and Ti). Issue 25 (3rd June 2013) - Kulkarni, A.; Schoen, J. C.; Doll, K.; Jansen, M.
Abstract Based on ab initio calculations at various pressures meta(stable) modifications of CaN2, LaN2, and TiN2 are predicted.